Mathematical modeling of two-dimensional size exclusion chromatography model comparing fully porous and core-shell particles - Uche∗†, U.D.; Salaudeen‡, A.O.; Okechi, N.F.; Ahmad¶, A.G. (International Journal of Mathematical Analysis and Modelling, 2023)
This work presents a comparison of fully porous and core-shell particles for size-exclusion chromatography. A two-dimensional general rate model is formulated for a column of cylindrical geometry. The model equations consist of a system of partial differential equations. Semi-analytical solutions are obtained for the formulated model equations by applying Hankel and Laplace transformations one after the other. This task is aimed at theoretically investigating and comparing the separation process output for both fully porous and core-shell particles for size-exclusion chromatography operations under isothermal conditions. The simulations in this work are used to demonstrate the size-exclusion effect for fully porous and core-shell particles and the results show better resolution of elution profiles are obtainable for some range of values of core radius fraction.